Manajemen Strategi Pengembangan Pariwisata Terhadap Dunia Pendidikan Dan Perekonomian Masyarakat (Studi Kasus Pada Pelaku Usaha Wisata Pantai Tanjoh Desa Tanjung Luar) - Sirajun Nasihin; Ayatullah; Herianto (Pendidikan Al-Gafari, 2023)
Tanjoh Beach, Tanjung Luar Village is a village fisherman. His name is known Because as produces squid the largest in East Lombok. Then build dock 2 for needed transportation goods For support dock before. Name project development suddenly stalled without clarity. See the situation the, group aware tour local named Pokdarwis Tanjoh also took the initiative to take advantage and juggle the wharf area. Study This aim For know is development strategy management destination tour Tanjoh in the village of Tanjung Luar has an impact on repairing economics and improving the world of education in the village of Tanjung Luar. Study This characteristic descriptive qualitative. The sources of data used are primary data and secondary data. With the use method of data collection i.e. observation, interview, and documentation. Research results show that component development tourist consists of market analysis, utilization technology, development network cooperation, coordination sector support, promotion, monitoring, and evaluation program implementation. Development Tanjoh Beach tourism, Tanjung Luar Village provides impact to enhancement quality education child perpetrator businesses in tourist areas. The community of Tanjung Luar Village felt a significant impact in open opportunity businesses, opportunity business that consists of business selling food soft, and drink-in packaging, business service like service parking, renting boat, renting rubber tires or tool swimming, and services parking. Income received by the community from the results of business being carried out can sufficiently need family, education, and health.